MACRO AND MICRO-NUTRIENTS VARIATION AMONGST SIX GENOTYPES OF BRASSICA JUNCEA (MUSTARD) INFECTED WITH ALBUGO CANDIDA (WHITE RUST) - K. K. MISHRA; S. J. KOLTE (The Bioscan, 2014)
The changes in macro and micro-nutrients were investigated in cotyledonary and true leaves of six genotypes of Brassica juncea: Kranti, Varuna, EC-399296, EC-399299, EC-399313 and EC-399301 inoculated with Albugo candida. The nitrogen content was decreased and was highest in genotype Varuna (0.66% dry wt.) followed by Kranti (0.64% dry wt.) after inoculation at cotyledonary stage while lowest was observed in EC-399299 (0.49% dry wt.). At true leaf stage, genotype Kranti had highest nitrogen content (0.78 and 0.82% at 14 and 21 DAI, respectively) while lowest was recorded in EC-399301 (0.56 and 0.66 at 14 and 21 DAI, respectively). Similarly, higher content of Zinc and manganese were recorded in true leaves of EC 399301 at 21 DAI (44.86 and 60.92 μg/ g dry wt., respectively). The susceptible response of genotype EC-399301 at cotyledonay stage and resistant reaction at true leaf stage might be because of having higher content of nitrogen, lower content of zinc and manganese at cotyledonay stage and vice-versa. However, phosphorus and potassium content appear to play no significant role in making the differences in reaction to white rust at cotyledonary and true leaf stages of EC- 399301.